Minimizing the risk of injury to the popliteal artery during pullout repair of medial meniscus posterior root tears: A cadaveric study - Yuta Mori; Tomoaki Kamiya; Shinichiro Okimura; Kousuke Shiwaku; Yohei Okada; Atsushi Teramoto; Toshihiko Yamashita (Elsevier, 2024)
Background: The purpose of this study was to investigate the positional effect of guide pins used in the transtibial pullout repair of medial meniscus posterior root tears on the popliteal artery. Methods: We used eight cadaveric knees. Two 2.4-mm guide pins were inserted into the posterior root of the medial meniscus at 50° to the articular surface from the medial edge of the tibial tuberosity (anteromedial group) and the anterior edge of the medial collateral ligament (posteromedial group) using an aiming guide placed at the posterior root attachment of the medial meniscus from the anteromedial portal. The posterior capsule was dissected, and the popliteal artery was identified. The positional effect of the guide pins on the popliteal artery was photographed arthroscopically at 0°, 30°, 60°, and 90° knee flexion angles. The popliteal artery diameter and the minimum distance between the popliteal artery center and the guide pin tip were measured. Results: At 90° knee flexion, most of the guide pins in the anteromedial (6 knees; 75 %) and posteromedial groups (7 knees; 87.5 %) collided with the femoral intercondylar wall. The rate of collision was significantly higher at the 90° knee flexion position than that at other angles (p = 0.02). The average shortest distance between the popliteal artery center and the guide pin tip at 0° knee flexion in the posteromedial group (5.4 mm ± 3.4 mm) was significantly greater than that at other knee flexion angles, although the mean distance in the posteromedial group was so negligible that the guide pin could penetrate the popliteal artery. Conclusions: Knee flexion at 90° causes less damage to the popliteal artery during the transtibial pullout repair of medial meniscus posterior root tears.